Implementation of Team Teaching in a Secondary Teacher Education College - Reeta Rai; Kinley Kinley; Choeda Choeda; Thinley Wangchuk; Tashi Pelden (Journal of Research in Education and Pedagogy, 2026)
Team teaching is an instructional approach involving joint planning, delivery, and assessment. This study explored the implementation of the team teaching approach in a secondary teacher education programme to address its limited empirical research in Bhutan. In Bhutan, the structure of teacher education programmes requires that pedagogical modules be delivered through team teaching to ensure a shared understanding of theory and practice between tutors and pre-service teachers. However, the team teaching approach is not implemented in practice and remains largely theoretical. This study examined how team teaching influenced pre-service teachers’ learning experiences and tutors’ professional development by involving 40 pre-service teachers and five tutors who carried out team teaching in a module called Skills for Effective Teaching. An action research design was used to study its implementation through iterative cycles of planning, action, observation, and reflection. Data were collected through semi-structured survey questionnaires and interviews at baseline and endline phases. Quantitative data were analysed using descriptive statistics, while qualitative data were analysed thematically. Findings indicated that team-teaching enhanced the application of theory into practice, content understanding, communication, engagement, and overall learning compared to single-tutor instruction. Tutors also reported improved collaboration, reflective practice, and professional growth by integrating expertise and peer support. However, challenges like limited time for collaborative planning, inconsistent guidance, and coordination issues were encountered. The study concludes that team teaching is an active instructional approach that enriches learning and professionalism. However, its effective implementation requires common expertise, scheduled planning and discussion time, clear communication, and institutional support.